Role of neutrophils in acute lung injury and repair - Downey, Gregory (Henry Stewart Talks, 2011)
Clinical problem of acute lung injury and ARDS, physiological role of neutrophils in host defense and innate immunity, pathological role of neutrophils in inflammatory tissue injury in general and in acute lung injury, mechanisms of damage to the lung epithelium by neutrophils, paradoxical role of neutrophils in initiating repair processes